Facilitation of sodium intake by combining noradrenaline into the lateral parabrachial nucleus with prazosin peripherally - Gasparini, S. [UNESP]; Gomide, J. M C [UNESP]; Andrade-Franzé, G. M F [UNESP]; Totola, L. T.; De Luca, L. A. [UNESP]; Colombari, Débora Simões de Almeida [UNESP]; Paula, Patricia Maria de [UNESP]; Moreira, T. S.; Menani, José Vanderlei [UNESP] (Elsevier, 2013)
Injections of noradrenaline into the lateral parabrachial nucleus (LPBN) increase arterial pressure and 1.8% NaCl intake and decrease water intake in rats treated with the diuretic furosemide (FURO) combined with a low dose of the angiotensin converting enzyme inhibitor captopril (CAP). In the present study, we investigated the influence of the pressor response elicited by noradrenaline injected into the LPBN on FURO + CAP-induced water and 1.8% NaCl intake. Male Holtzman rats with bilateral stainless steel guide-cannulas implanted into LPBN were used. Bilateral injections of noradrenaline (40 nmol/0.2 μl) into the LPBN increased FURO + CAP-induced 1.8% NaCl intake (12.2 ± 3.5, vs., saline: 4.2 ± 0.8 ml/180 min), reduced water intake and strongly increased arterial pressure (50 ± 7, vs. saline: 1 ± 1 mm Hg). The blockade of the α1 adrenoceptors with the prazosin injected intraperitoneally abolished the pressor response and increased 1.8% NaCl and water intake in rats treated with FURO + CAP combined with noradrenaline injected into the LPBN. The deactivation of baro and perhaps volume receptors due to the cardiovascular effects of prazosin is a mechanism that may facilitate water and NaCl intake in rats treated with FURO + CAP combined with noradrenaline injected into the LPBN. Therefore, the activation of α2 adrenoceptors with noradrenaline injected into the LPBN, at least in dose tested, may not completely remove the inhibitory signals produced by the activation of the cardiovascular receptors, particularly the signals that result from the extra activation of these receptors with the increase of arterial pressure. © 2013 Elsevier Inc.
Keywords: Baro and volume receptors; Blood pressure; Noradrenaline; Parabrachial nucleus; Sodium appetite